Antioxidant and Anti-Inflammatory Profiles of Spent Coffee Ground Extracts for the Treatment of Neurodegeneration. (20th May 2021) - Angeloni, Simone; Freschi, Michela; Marrazzo, Pasquale; Hrelia, Silvana; Beghelli, Daniela; Juan-García, Ana; Juan, Cristina; Caprioli, Giovanni; Sagratini, Gianni; Angeloni, Cristina
Abstract : Spent coffee grounds (SCGs), waste products of coffee beverage production, are rich in organic compounds such as phenols. Different studies have demonstrated phenol beneficial effects in counteracting neurodegenerative diseases. These diseases are associated with oxidative stress and neuroinflammation, which initiates the degeneration of neurons by overactivating microglia. Unfortunately, to date, there are no pharmacological therapies to treat these pathologies. The aim of this study was to evaluate the phenolic content of 4 different SCG extracts and their ability to counteract oxidative stress and neuroinflammation. Caffeine and 5- O -caffeoylquinic acid were the most abundant compounds in all extracts, followed by 3- O -caffeoylquinic acid and 3, 5- O -dicaffeoylquinic acid. The four extracts demonstrated a different ability to counteract oxidative stress and neuroinflammation in vitro. In particular, the methanol extract was the most effective in protecting neuron-like SH-SY5Y cells against H2 O2 -induced oxidative stress by upregulating endogenous antioxidant enzymes such as thioredoxin reductase, heme oxygenase 1, NADPH quinone oxidoreductase, and glutathione reductase. The water extract was the most effective in counteracting lipopolysaccharide-induced neuroinflammation in microglial BV-2 cells by strongly reducing the expression of proinflammatory mediators through the modulation of the TLR4/NF- κ B pathway. On these bases, SCG extracts could represent valuable nutraceutical sources for the treatment of neurodegeneration.